Analisis Bahaya Kebisingan Pada Proyek Rumah Susun ASN 2 IKN Kalimantan Timur - Faiq Pandu Mahajana; Muhammad Faisal Fadhil (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Noise pollution from construction projects is a critical issue, especially in high-density areas such as the ASN 2 housing projects in IKN. In this study, noise levels were measured at 29 predetermined points using a Sound Level Meter (SLM) during three time intervals to assess variations in noise intensity. Noise mapping was performed using the Surfer 24 application to visualise the spatial distribution of noise and identify areas exceeding the noise threshold of 85 dB, as regulated by Permenaker No. 5/2018. The results showed that several locations exceeded the permissible exposure limits, with Daily Noise Dose (DND) values exceeding 100%, and these areas were classified as hazardous. Mitigation measures include technical controls (equipment modifications and noise barriers), administrative controls (shift rotation and warning signs) and personal protective equipment (PPE) such as earplugs. These measures aim to protect the health of workers and reduce the risk of noise-induced hearing loss (NIHL).